2020
DOI: 10.1177/1474904120923184
|View full text |Cite
|
Sign up to set email alerts
|

Feeling at home in school: Migrant youths’ narratives on school belonging in Flemish secondary education

Abstract: In Flanders, students with a migration background are highly overrepresented in the lower-status vocational and technical tracks, experience more grade retention and school and track mobility and have a higher risk of leaving school early than their native peers. The authors aim to shed light on the complexity of school belonging and its significance in these young people’s pursuit of a diploma. The analysis focuses on the lived experiences of three young individuals and reconstructs their trajectories from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 46 publications
(72 reference statements)
0
18
1
Order By: Relevance
“…School belonging has been established in the literature as a positive predictor of educational achievement, academic self-efficacy and attitudes (Fong Lam et al, 2015;Niehaus et al, 2012), andwellbeing (Kia-Keating &Ellis, 2007;Nuttman-Shwartz, 2019;Scharpf et al, 2020). Previous research has shown that positive peer relationships, connectedness with friends (Allen et al, 2018;Ambrose, 2020;Delgado et al, 2016;DeNicolo et al, 2017;Van Caudenberg et al, 2020), and parental support at home (Allen et al, 2018;Hu & Wu, 2020) are linked to increased feelings of school belonging. Research has also found that school belonging forms a protective factor against the development of mental health problems (Kia-Keating & Ellis, 2007;Nuttman-Shwartz, 2019;Scharpf et al, 2020).…”
Section: Theoretical Underpinnings Of School Belonging and Literature...mentioning
confidence: 99%
See 3 more Smart Citations
“…School belonging has been established in the literature as a positive predictor of educational achievement, academic self-efficacy and attitudes (Fong Lam et al, 2015;Niehaus et al, 2012), andwellbeing (Kia-Keating &Ellis, 2007;Nuttman-Shwartz, 2019;Scharpf et al, 2020). Previous research has shown that positive peer relationships, connectedness with friends (Allen et al, 2018;Ambrose, 2020;Delgado et al, 2016;DeNicolo et al, 2017;Van Caudenberg et al, 2020), and parental support at home (Allen et al, 2018;Hu & Wu, 2020) are linked to increased feelings of school belonging. Research has also found that school belonging forms a protective factor against the development of mental health problems (Kia-Keating & Ellis, 2007;Nuttman-Shwartz, 2019;Scharpf et al, 2020).…”
Section: Theoretical Underpinnings Of School Belonging and Literature...mentioning
confidence: 99%
“…School belonging is often a complex experience for migrant students whereby personal emotions and formal representations and norms of belonging interact with and conflict with each other (e.g., Ambrose, 2020;Gao et al, 2019;Puroila et al, 2021;Souto-Manning, 2021;Van Caudenberg et al, 2020;Yuval-Davis, 2004). DeNicolo et al ( 2017) identify the quality of teacher-student and peer relationships, as well as migrant students' agency, as key components in creating a positive sense of belonging for migrant students.…”
Section: Theoretical Underpinnings Of School Belonging and Literature...mentioning
confidence: 99%
See 2 more Smart Citations
“…Nowadays, belonging is used as an analytical category in sociology, geography, anthropology, psychology, political science, history, and law to address topics such as citizenship, migration, and identity. It is particularly relevant to underline the work developed in the educational field through the use of this concept, asserting that "students who feel little or no connection to their school are more likely to suffer from a range of negative emotions and behavioural problems, tend to show lower school engagement and are more likely to be absent from school and to leave school early" [56] (p. 2). Other authors refer to 'modes of belonging', as an approach to apprehend the different attachment forms to places, groups, cultures, etc., [57].…”
Section: Belongingmentioning
confidence: 99%